ثروات المغرب الأوسط النباتية و الحيوانية خلال العصر الوسيط من خلال مصنفات الرحلة والجغرافيا - بن عربة, محمد; بوسالم, أحلام (جامعة الوادي - University of Eloued, 2019)
The books of the journey and geography are one of the most important of sources that chronicle the culturale aspects Algeria during the middle ages ,it contains valuable information and rare details, its countarparts in the rest of the sources because those who wrote it visited this land and mingled with its inhabitants and ate its good things and observed the most important transformations in its cities and countryside . distributed among the various fields between political and social and even nodal but the most important that have been assosiated with economic life and described its transactions and knew ways and methods and systems and talked to many about the natural wealth, especially the plant and animal product .
مقال
Keywords: المغرب الأوسط,كتب الرحلة والجغرافيا,الثروات الطبيعي’الثروة النباتية,الثروة الحياوانية; Middle East - Travel and geography books - Natural resources - Plant wealth - animal product